Finding audrey eaudiobook - Kinsella, Sophie (Listening Library, 2015)
A New York Times  Bestseller & A ZOELLA Book Club Pick! From the #1 New York Times bestselling author of the Shopaholic series comes a terrific blend of comedy, romance, and psychological recovery in a contemporary YA novel sure to inspire and entertain.   An anxiety disorder disrupts fourteen-year-old Audrey’s daily life. She has been making slow but steady progress with Dr. Sarah, but when Audrey meets Linus, her brother’s gaming teammate, she is energized. She connects with him. Audrey can talk through her fears with Linus in a way she’s never been able to do with anyone before. As their friendship deepens and her recovery gains momentum, a sweet romantic connection develops, one that helps not just Audrey but also her entire family.